A bibliography on recent advancement in thermal energy storage – a mini review - Roslan, Mohammad Fikrey; Abd Karim, Rafidah (Academica Press Solutions, 2022)
The thermal energy storage (TES) system is one of the most innovative technologies available for meeting long-term energy demands. Energy storage technology has demonstrated its ability to close the energy gap between supply and demand. The storage of thermal energy (TES) building integration is expected to reduce energy demand shortages while also allowing for better energy management in the construction industry. This paper will review about recent advancements in thermal energy storage which is in mini-review. There is some point that is highlighted in the review. There is sensible heat storage, latent heat storage and thermal chemical storage and the advantage of thermal energy storage. In this review paper, recent advancement has been studied and discussed, most commercial thermal energy storage was the sensible heat storage which is most cheap and most ready to use in recent technology. While future research is needed for giving confidence to the audience to use their system, which latent heat storage and thermochemical storage provide high energy capacity and high temperature for storing effect. These technologies were come in to track which has the advantage of their effectiveness.